1997
DOI: 10.12968/bjon.1997.6.13.746
|View full text |Cite
|
Sign up to set email alerts
|

Drug administration in day centres for people with learning disabilities

Abstract: A study was made of the problems associated with the need to administer medicines at day centres for people with learning disabilities. In Leicestershire, 167 (13%) of 1317 people with learning disabilities who attended day centres required the administration of medicines. The percentage of attenders requiring drug administration varied from day centre to day centre (minimum 4%, maximum 23%). Antiepileptics were the most commonly administered drugs, followed by antipsychotics. The administration of medicines t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…However, several sources referred to it, while focusing on other parameters and variables. The information extracted from these sources largely clustered on themes of complexity (Branford et al, 1997; Burrow and Rimmer, 1997), risks (Hom et al, 2015; Rasaratnam et al, 2004; Tan et al, 2015; Van Den Bemt et al, 2007) and team makeup (Ellenor and Frisk, 1977; Van Den Bemt et al, 2007; Venables et al, 2015) with repeated emphasis on education and training (Abbott et al, 2014; Bosner and Belfiore, 2001; Buelow and Shore, 2010; Rasaratnam et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, several sources referred to it, while focusing on other parameters and variables. The information extracted from these sources largely clustered on themes of complexity (Branford et al, 1997; Burrow and Rimmer, 1997), risks (Hom et al, 2015; Rasaratnam et al, 2004; Tan et al, 2015; Van Den Bemt et al, 2007) and team makeup (Ellenor and Frisk, 1977; Van Den Bemt et al, 2007; Venables et al, 2015) with repeated emphasis on education and training (Abbott et al, 2014; Bosner and Belfiore, 2001; Buelow and Shore, 2010; Rasaratnam et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…In a descriptive mixed-methods study, Branford et al (1997) identified the complexity of medication management, especially when it occurred across a number of locations (Burrow and Rimmer, 1997) as can be typical in intellectual disability settings. Describing the preparation, transport, storage, oversight and administration of this process, they highlighted the importance of collaboration and communication in minimising risk of medication errors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations